Determination of Key Inflection Points for Maladaptive Responses in US Nurses During the Pandemic: A Network Analysis - Fan Li RN, PhD; Umit Tokac PhD; Kimberly Werner PhD; Anne F. Fish RN, PhD; Qingqing Lou RN, PhD (SAGE Publishing, 2022)
Introduction During the pandemic, the nursing workforce is experiencing overwhelming workloads that carry a heavy psychological burden. A wide variety of psychological responses to the COVID-19 pandemic have been studied in nurses globally, but many are not studied or understudied in US nurses. Theoretical underpinnings of the current study are based on the disaster component of the Middle-Range Theory of Nurses' Psychological Trauma. Objective To explore the associations of psychological responses (life satisfaction, perceived stress, posttraumatic stress disorder [PTSD] symptomatology, attitude toward life, and compassion satisfaction), years of experience, and general health in US nurses during the COVID-19 pandemic using network analysis. Methods A cross-sectional study was conducted using an online survey from October to November 2020 in US nurses. Network analysis was used to model the data and analyze the centrality indices of betweenness, closeness, and strength. Data were reported according to the Strengthening the Reporting of Observational studies in Epidemiology (STROBE) checklist. Results In 128 nurses, 19.35% of nurses had probable PTSD. Network analysis showed strong significant correlations between life satisfaction and perceived stress (negative), between perceived stress and PTSD symptomatology (positive), and between attitude toward life and compassion satisfaction (positive). Conclusion Low life satisfaction, high perceived stress, and low attitude toward life are key inflection points that signal the need for psychological intervention in the US nursing workforce during the continued pandemic. Based on 2021 Tri-Council of Nursing COVID-19 Report and the 2022 International Council of Nurses guideline, healthcare should implement scalable, system-level interventions to reduce psychological burden during the pandemic. The current study suggests targets for such intervention, which may promote a healthier, more effective US nursing workforce.